Vergil i uorden - Bülow-Jacobsen, Adam (AIGIS, 2024)
O.Xeron inv. 871. 26×29 cm. From the Roman fortress Xeron Pelagos on the road from Coptos to Berenice. Dated by stratigraphy and palaeography to late second-early third century. The text is Aeneid. Not a school-text, but quoted from memory in haphazard order. Orthographic errors are abundant, and all common in vulgar Latin.